2022
DOI: 10.3390/ijms231911211
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Extracellular Vesicles as Proposed Therapy in a Rat Model of Cerebral Small Vessel Disease

Abstract: Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) have been employed in the past decade as therapeutic agents in various diseases, including central nervous system (CNS) disorders. We currently aimed to use MSC-EVs as potential treatment for cerebral small vessel disease (CSVD), a complex disorder with a variety of manifestations. MSC-EVs were intranasally administrated to salt-sensitive hypertension prone SBH/y rats that were DOCA-salt loaded (SBH/y-DS), which we have previously shown is a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…This can impact the development of SSH by affecting the activity of TH17 cells through various mechanisms involving the gut flora ( 13 , 38 , 39 ). Extracellular vesicles (EVs) play a crucial role in SSH by transporting proteins, nucleic acids, and lipids among cells ( 41 ). Urinary EVs are being researched as possible biomarkers for hypertension, as they contain proteins related to renal sodium transport, which is important in hypertension development ( 42 ).…”
Section: Gut Microbiota Regulates the Th17 Axis And Sshmentioning
confidence: 99%
See 1 more Smart Citation
“…This can impact the development of SSH by affecting the activity of TH17 cells through various mechanisms involving the gut flora ( 13 , 38 , 39 ). Extracellular vesicles (EVs) play a crucial role in SSH by transporting proteins, nucleic acids, and lipids among cells ( 41 ). Urinary EVs are being researched as possible biomarkers for hypertension, as they contain proteins related to renal sodium transport, which is important in hypertension development ( 42 ).…”
Section: Gut Microbiota Regulates the Th17 Axis And Sshmentioning
confidence: 99%
“…Higher levels of NCC or phosphorylated NCC in urinary EVs are found in hypertensive patients, indicating the importance of EVs in hypertension. Other markers linked to hypertension, like Inducible Vitamin D Gene 2 protein and hsa-miR-4516, have also been identified in EVs, showing potential for early detection of hypertension ( 41 44 ). Thus, the gut microbiota may affect blood pressure in SSH by controlling salt absorption and metabolism through extracellular vesicles, potentially worsening the condition.…”
Section: Gut Microbiota Regulates the Th17 Axis And Sshmentioning
confidence: 99%
“…MSC-EVs decrease IL-1β and IL-6 expression in lipopolysaccharides-stimulated BV2 cells and attenuate inflammation [ 64 ]. Researchers built animal models of CSVD using salt-loaded SBH/y rats to induce hypertension and found that cognitive deficits improved after MSC-EV treatment [ 64 ]. However, the underlying mechanisms require further in-depth studies [ 64 ].…”
Section: Intercellular Communications That Evs Mediate In Vascular Di...mentioning
confidence: 99%
“…Researchers built animal models of CSVD using salt-loaded SBH/y rats to induce hypertension and found that cognitive deficits improved after MSC-EV treatment [ 64 ]. However, the underlying mechanisms require further in-depth studies [ 64 ]. Most studies have focused on EVs from the serum or plasma of patients and healthy volunteers as diagnostic markers for CSVD; however, a large gap exists in the understanding of the pathological roles and therapeutic potential of EVs in this disease.…”
Section: Intercellular Communications That Evs Mediate In Vascular Di...mentioning
confidence: 99%
“…Several studies have used the rat model to study the role of EVs in spinal cord injuries (143,144) and repetitive stress (145). Rat models have also been used to investigate the therapeutic potential of EVs to treat diseases such as small cerebral vessel disease (146), colo-cutaneous post-surgical fistula (147), and congenital diaphragmatic hernia (148).…”
Section: Ev Tracking Animal Modelsmentioning
confidence: 99%